2019
DOI: 10.1016/j.isci.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Processing Factor Y14 Participates in DNA Damage Response and Repair

Abstract: SummaryDNA repair deficiency leads to genome instability and hence human disease. Depletion of the RNA processing factor Y14/RBM8A in cultured cells or Rbm8a haplodeficiency in the developing mouse cortex results in the accumulation of DNA damage. Y14 depletion differentially affected the expression of DNA damage response (DDR) factors and induced R-loops, both of which threaten genomic stability. Immunoprecipitation coupled with mass spectrometry revealed DDR factors as potential Y14-interacting partners. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Immediately after their synthesis in the cytoplasm, RBM8A and MAGOH assemble into a heterodimer, which is transported by importin 13 (IPO13) to the nucleus [ 21 , 22 ] ( Figure 1 C). Although the heterodimer likely represents the biologically predominant form, RBM8A has also been described to have EJC-independent functions, for example as a factor involved in DNA damage repair and modulator of processing body formation [ 23 , 24 ]. Still, it remains to be investigated to what extent RBM8A and MAGOH have functions separate from each other or as a heterodimer outside the EJC.…”
Section: Components Of the Ejcmentioning
confidence: 99%
“…Immediately after their synthesis in the cytoplasm, RBM8A and MAGOH assemble into a heterodimer, which is transported by importin 13 (IPO13) to the nucleus [ 21 , 22 ] ( Figure 1 C). Although the heterodimer likely represents the biologically predominant form, RBM8A has also been described to have EJC-independent functions, for example as a factor involved in DNA damage repair and modulator of processing body formation [ 23 , 24 ]. Still, it remains to be investigated to what extent RBM8A and MAGOH have functions separate from each other or as a heterodimer outside the EJC.…”
Section: Components Of the Ejcmentioning
confidence: 99%
“…A high frequency of lymphomas has been observed in Trp53 -null mice (Donehower et al, 1995). Because Y14 is also essential for maintaining genome stability (Chuang et al, 2019), concomitant loss of Rbm8a and p53 may likely increase the incidence of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional allele of Rbm8a ( Rbm8a f/f ) was created by insertion of loxP sites flanking its exon 2 and 6 using the CRISPR/Cas9 system (Chuang et al, 2019). Rbm8a f/f mice were then crossed with Pf4-Cre +/- mice (Tiedt et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RBPs have been shown to contribute both directly and indirectly to genome stability. For example, the loss of pre-mRNA splicing or mRNA export factors can favour the accumulation of RNA:DNA hybrids (R-loops) that can be processed to DSBs (Chuang et al, 2019;Li and Manley, 2005). In addition, an increasing number of studies have shown that several RBPs are recruited to sites of DNA damage and participate in DSB repair (Mikolaskova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%